2015
DOI: 10.1039/c5ra18422c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of pyrimidine-containing hexaarylbenzene derivatives

Abstract: Three claw-shaped hexaarylbenzene derivatives containing pyrimidines have been synthesized by cobalt-catalyzed corresponding tolan derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…198 The purpose of the introduction of carboxylic groups is to enhance the degree of hydrogen bonding, metal-binding abilities, and self-assembly properties. Similar to the previous report, 197 isomers 105 and 106 (Figure 52) were produced from cyclotrimerization of respective unsymmetrical 1,2-disubstituted acetylene. The flocculant nanostructures of derivatives 105 turned into beltlike structures after interaction with Ag + ions, which led to a red-shift in the emission band, whereas no such switching in aggregates or shift in emission band were observed in the case of derivative 106.…”
Section: Chemical Reviewssupporting
confidence: 86%
See 1 more Smart Citation
“…198 The purpose of the introduction of carboxylic groups is to enhance the degree of hydrogen bonding, metal-binding abilities, and self-assembly properties. Similar to the previous report, 197 isomers 105 and 106 (Figure 52) were produced from cyclotrimerization of respective unsymmetrical 1,2-disubstituted acetylene. The flocculant nanostructures of derivatives 105 turned into beltlike structures after interaction with Ag + ions, which led to a red-shift in the emission band, whereas no such switching in aggregates or shift in emission band were observed in the case of derivative 106.…”
Section: Chemical Reviewssupporting
confidence: 86%
“…Recently, Zhang et al 197 reported synthesis of pyrimidinecontaining HPB derivatives 102−104 (Figure 52) through cyclotrimerization of appropriate disubstituted acetylenes. The symmetric 1,2-disubstituted acetylene resulted in formation of a single major product 102, whereas unsymmetrical 1,2-disubstituted counterparts produced two isomers, 103 and 104, under similar conditions.…”
Section: Chemical Reviewsmentioning
confidence: 99%